Investigation of cure and mechanical properties of deproteined natural rubber-g-poly(methyl methacrylate) - Nhan, Nguyen Thi; Dung, Tran Anh; Khanh, Pham Duy; Thuong, Nghiem Thi; Tung, Nguyen Huu; Nghia, Phan Trung; Thuy, Tran Thi (Vietnam Journal of Chemistry, 2016)
Investigation of cure and mechanical properties of graft copolymer of deproteinized natural rubber (DPNR) with methyl methacrylate (MMA) prepared by graft copolymerization in latex was presented in this work. It is determined that the increase in scorch time, cure time, hardness and tear strength of the graft copolymer were depended on monomer concentration. With the monomer concentration of 15 g/100 g rubber, the increase of hardness and tear strength are 68 % and 66 %, respectively, compared to DPNR. Besides, there are increasing trends of tensile strength and elongation at break. The optimum concentration of MMA monomer is found at 15 g/100 g-rubber. At this monomer concentration, the hardness and tear strength of the graft copolymer increased, whereas the elongation at break and the tensile strength decreased a bit compared to the natural rubber. Keywords. Natural rubber, polymethyl methacrylate, grafted copolymer, curing properties, mechanical properties.